Malaria Density in Peripheral Blood Smear on Positive Cases of Malaria on Residences of Jaro South Kalimantan - Nurmansyah, Dian; Khasanah, Maulisa; Wahyuni, Rizka Ayu; Puspawati, Puspawati (Jurnal Analis Medika Biosains (JAMBS), 2024)
Malaria, a severe infectious disease caused by Plasmodium parasites, remains a significant health challenge in endemic regions of Indonesia, particularly in areas with favorable environmental conditions for Anopheles mosquitoes. The liver is a critical organ involved in the early stages of malaria infection. This study investigates malaria density in confirmed malaria cases in Jaro District, South Kalimantan. The aims of this study was to determine the parasitemia density in individuals diagnosed with malaria in the Jaro District, contributing to the understanding of malaria severity in this region. A descriptive survey approach was employed to measure malaria density in 15 respondents with confirmed Plasmodium falciparum infections. Total sampling was used, and blood specimens were collected and analyzed in the clinical pathology laboratory of RS Badaruddin Kasim. Blood smears were stained using 3% Giemsa stain, and parasitemia density was determined microscopically following the Ministry of Health's 2012 guidelines. The study identified varying levels of parasitemia density among the respondents: 33.3% had a low parasitemia density (+), 20% had moderate densities (++ and +++), and 26.7% exhibited high density (++++). The highest proportion of cases showed a low parasitemia density. The analysis of malaria density in the Jaro District reveals significant variability in parasitemia levels among patients. This variability highlights the importance of continuous monitoring and tailored interventions to manage malaria effectively in endemic regions. Understanding parasitemia density is crucial for assessing disease severity and implementing effective treatment